Semaglutide ameliorates metabolism and hepatic outcomes in an NAFLD mouse model - Niu, Shu; Chen, Shuchun; Chen, Xing; Ren, Qingjuan; Yue, Lin; Pan, Xiaoyu; Zhao, Huiying; Li, Zelin; Chen, Xiaoyi (Frontiers in Endocrinology, 2022)
Purpose: The aim of this study was to evaluate changes in body weight, liver weight, blood glucose, liver injury markers, pro-inflammatory factors and oxidative stress marker levels in obese mice with HFD induced NAFLD after semaglutide use. Patients and methods: The 24 C57BL6J mice were randomly divided into three groups (NCD, HFD and Sema) for the assessment of metabolic status, inflammatory factor and oxidative stress marker levels, liver histopathology in mice. Liver metabolomics was determined by liquid chromatography/mass spectrometry (LC-MS) method. Results: The mice body weight, liver weight, blood glucose, TG, TCHO, LDL and pro-inflammatory factors were significantly reduced after semaglutide. Meanwhile, semaglutide increased the SOD level. Semaglutide treatment significantly improved the pathological changes such as hepatocyte steatosis, balloon degeneration and lymphoid foci by HE. It also significantly reduced lipid droplet by Oil Red O. The mitochondria were swollen, the volume increased, the cristae were partially broken and reduced, the intramembrane matrix was partially dissolved, and the mitophagy structure was visible in the visual field. There were 6 metabolites down-regulated and 2 metabolites significantly up-regulated after semaglutide treatment. Conclusions: Semaglutide can reduce blood glucose level and liver fat accumulation and play an anti-inflammatory role in advanced NAFLD that due to the effects of HFD.